Surface PEGylated Cancer Cell Membrane-Coated Nanoparticles for Codelivery of Curcumin and Doxorubicin for the Treatment of Multidrug Resistant Esophageal Carcinoma - Gao, Yi; Zhu, Yue; Xu, Xiaopeng; Wang, Fangjun; Shen, Weidong; Leng, Xia; Zhao, Jiyi; Liu, Bingtuan; Wang, Yangyun; Liu, Pengfei (Frontiers in Cell and Developmental Biology, 2021)
Objective: Preparing a biomimetic nano-targeting drug modified by cancer cell membrane and investigating its efficiency in treating multidrug-resistant (MDR) esophageal carcinoma. Methods: The degradable PLGA nanoparticles (NPs) co-loaded with doxorubicin (DOX) and curcumin were prepared using the solvent evaporation method. TE10 cell membrane and DSPE-PEG were then coated on the PLGA NPs by membrane extrusion method to prepare the PEG-TE10@PLGA@DOX-Cur NPs (PMPNs). The size and zeta potential of the PMPNs were analyzed by lazer particle analyzer, and the morphology of PMPNs was observed by transmission electron microscope. The protein on TE10 cell membrane was analyzed by gel electrophoresis. In vitro cell uptake assay was performed to evaluate the homologous targeting ability of PMPNs. The DOX-resistant esophageal cancer cell model TE10/DOX was established through high-dose induction. The in vitro anti-tumor effect of PMPNs was assessed through CCK-8, clone formation assay and flow cytometric analysis. Tumor-bearing Balb/c mouse model was constructed to evaluate the anti-tumor effect in vivo and the biological safety of PMPNs. Results: The prepared PMPNs had a regular spherical structure with an average diameter of 177 nm, the cell membrane was well coated on its surface. Cell uptake experiments showed that PMPNs directly target TE10 and TE10/DOX cells. The drug efficacy experiments showed that PMPNs effectively inhibit the growth of DOX-resistant esophageal carcinoma, and have slight damage to liver, kidney and heart function. Conclusions: In this study, a biomimetic nano-drug delivery system PMPNs was successfully prepared, which overcome the MDR of tumor by co-delivering DOX and sensitizer curcumin. The PMPNs markedly improve the targeting and therapeutic effect of esophageal carcinoma, and reduce the toxic and side effects.